The element-free Galerkin method applied to the study of fully developed magnetohydrodynamic duct flows - Verardi, SLL; Machado, J. M.; Cardoso, JR (Institute of Electrical and Electronics Engineers (IEEE), 2002)
In this paper, the meshless method is introduced to magnetohydrodynamics. A numerical scheme based on the element-free Galerkin method is used to solve the laminar steady-state two-dimensional fully developed magnetohydrodynamic flow in a rectangular duct. Accurate and convergent solutions are achieved for low to moderately high Hartmann numbers.
Keywords: element-free Galerkin method; liquid metal flows; magnetohydrodynamics